Penguatan Sumber Daya Manusia Desa Tumbang Nusa Melalui Peningkatan Kesadaran Pendidikan dan Keterampilan Bahasa Inggris: Pengabdian - Maida Norahmi; Maria Arina Luardini; Natalina Asi; Akhmad Fauzan; Bahing; Lesly Martha Cecylia Meka; Olga Dona Retsi; Susanty; Erma Sujiyani; Sulamit Syeba; Yulitriana; Tutik Haryani; Risman Wanci (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Improving the quality of human resources in rural areas is a significant challenge in achieving equal education in Indonesia, particularly in areas such as Tumbang Nusa Village, Jabiren Raya District, Pulang Pisau Regency, Central Kalimantan. Low awareness of the importance of education and limited access to English language learning are factors that hinder the development of the younger generation's potential. This community service activity aims to increase the awareness and basic English language skills through a participatory and contextual approach based on the school community. The implementation method includes interactive training, song-based and visual learning, and joint reflection, face-to-face at partner schools. The results of the activity demonstrated high enthusiasm among participants, active engagement in the learning process, and increased motivation to learn English. This activity also strengthened collaboration between the community service team, the village, and the school as local partners. This activity suggests that the contextual and communicative approach is effective in developing learning awareness and language skills among students living in rural areas.